Preventing adolescent anemia in the patrilineal-Sasak culture: a qualitative study - Misroh Mulianingsih; Meyka Aris Yusron; Sopian Halid; M. Karjono (Universitas Gadjah Mada, 2026)
Purpose: This study aimed to explore the initial conditions of parenting practices, family perceptions of anemia, household support mechanisms, and social support from peers and schools among anemic adolescent girls within a patrilineal cultural context in North Lombok, West Nusa Tenggara, Indonesia. Methods: Using a qualitative approach, in-depth interviews were conducted with eight key informants—health workers, school representatives, and traditional leaders—in the working areas of Puskesmas (Public Health Centers) Gangga and Bayan, North Lombok. These locations were selected due to high anemia prevalence, strong patriarchal traditions, and extreme poverty. Data were collected through 60-minute face-to-face interviews using structured guides, recorded, and thematically analyzed following the Miles & Huberman framework. Results: Findings reveal low community awareness about adolescent anemia, with parenting still heavily influenced by tradition. Many families lack knowledge of the causes and consequences of anemia. Poor dietary habits in both areas further highlight the need for parental awareness of nutrition. Collaborative efforts among schools, health centers, and families are essential. Conclusion: Patrilineal culture and limited understanding of anemia prevention hinder efforts to prevent anemia; active family involvement in nutrition education is key to improving adolescent well-being.